Optimization of Human Resource Strategies by Investigating Employee Work Safety, Physical Health, and Psychological Well-Being Within a Moderated Well-Being Framework - Bilad, Dava Imadul; Agung Harikusuma Nugroho; Siti Mujanah; Achmad Yanu Alif Fianto (Jurnal Ekonomi, 2024)
The integration of well-being frameworks into human resource (HR) strategies has become essential for improving employee performance, retention, and organizational success. This study explores the impact of optimized HR strategies on organizational outcomes by focusing on employee safety, health, and well-being. The research employs a qualitative approach, analyzing key HR practices and their influence on workplace culture, employee satisfaction, and long-term sustainability. The objective of this study is to identify effective HR interventions that enhance employee well-being, leading to increased productivity, reduced turnover, and a positive organizational culture. The findings highlight that initiatives such as health programs, professional development opportunities, and flexible work arrangements significantly improve employee motivation and job satisfaction. Furthermore, prioritizing well-being reduces absenteeism and turnover rates, strengthening organizational stability and competitiveness. The discussion emphasizes the long-term benefits of investing in employee well-being, including enhanced innovation, resilience, and alignment with corporate social responsibility goals. Organizations that foster a supportive and inclusive workplace culture experience measurable improvements in both employee performance and business outcomes. In conclusion, HR strategies centered on well-being create sustainable organizational success by nurturing a healthy, engaged, and loyal workforce. These practices position organizations to adapt to challenges, drive growth, and maintain long-term competitiveness in an evolving global landscape.